Generation of Bio-electricity by Microbial Fuel Cells - Khan, Maksudur R.; Karim, M. R.; Amin, M. S. A. (International Journal of Engineering and Technology, 2012)
Renewable energy is an increasing need in our society. Microbial fuel cell (MFC) technology represents a new technology for the regeneration of electricity from what would otherwise be considered waste and can be a vital candidate for energy in this respect. Electricity directly generated by using bacteria while accomplishing wastewater treatment in MFC processes. The present study deals with performance of proton exchange membrane and cation exchange resin for ion transfer. The effect of dimension of Resin Bridge on electricity generation and COD removal was reported. A maximum voltage of 10.5 mV was observed at 400ppm of KMnO4 along with 400ml of dairy in an anode chamber. Average COD removal was in the range of 70% to 90%.